Legal Consequences and Sanctions for Consanguineous Marriages (Study of Pari City Village, Serdang Bedagai Regency) - Sendy, Beby; Syahranuddin, Syahranuddin; Artita, Tria Wahyu (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Consanguineous marriage is a marriage between individuals who are closely related by blood, which is prohibited by law and religion in Indonesia. This study aims to analyze the legal consequences and sanctions for consanguineous marriages, using a case study in Kota Pari Village, Serdang Bedagai Regency. The research method employs an empirical legal approach, utilizing interviews with village officials and an analysis of laws and regulations. The results show that consanguineous marriages are null and void, create complex child status issues, administrative obstacles, and have criminal implications. Sanctions that can be imposed include civil sanctions, a maximum imprisonment of seven years, as well as administrative, social, and customary sanctions. Continuous legal counseling and coordination between institutions are needed for effective prevention